An Investigation of Social Media as a Government Digital Public Relations Tool: The Nigerian Experience - Garba, Matyek Jimme; Yakubu, Kaze Solomon; Maryclaret, Ohaji Kelechi; Williams, Etumnu Emeka (Journal of New Media and Mass Communication, 2022)
The global media migration from traditional public relations to digital public relations is a new realm of research and the purpose of this study was to investigate social media as a digital public relations tool by the national and sub-national governments in Nigeria. The knowledge-gap on the frequency of usage of social media as a digital public relations tool by the Nigerian national and sub-national governments and the levels of e-participation by the online audience as at February 28, 2022, formed the basis of the investigation. The methodology of the study was the qualitative approach, with descriptive research as the research design. The findings of the chapter show that all national and sub-national governments use a minimum of two and a maximum of six social media accounts. Nevertheless, it was found out that the frequency of use ranged from monthly to yearly usage among all the 38 governments in Nigeria and the e-participation levels by the online audience are low. The chapter recommends that efforts should be made for all governments to adopt at least the top four social media platforms (Facebook, Twitter, YouTube, and Instagram) as digital public relations tools. Also, the full exploitation of Facebook as the foremost social media platform by governments in Nigeria due to its e-participation advantages of comments, shares, likes, and views is recommended. Finally, the study recommends that weekly usage of official government accounts and not governors' personal social media can boost e-participation levels in Nigeria.